The Effect of Initial State Error for Nonlinear Systems with Delay via Iterative Learning Control - Zhang Qunli (Advances in Mathematical Physics)
An iterative learning control problem for nonlinear systems with delays is studied in detail in this paper. By introducing the λ-norm and being inspired by retarded Gronwall-like inequality, the novel sufficient conditions for robust convergence of the tracking error, whose initial states are not zero, with time delays are obtained. Finally, simulation example is given to illustrate the effectiveness of the proposed method.